2017
DOI: 10.1016/j.foodres.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of structured lipids with behenic acid in the prevention of obesity

Abstract: Obesity affects all social classes, making it necessary to develop effective products that aid weight loss or help prevent weight gain. The objective of this work was to study the anti-obesity effects of structured lipids (SL) obtained by enzymatic interesterification, based on olive oil, soy oil and fully hydrogenated crambe oil. Twenty-four C57Bl/6 mice were distributed into four experimental groups according to the diet consumed: Control Diet (CD), Structured Lipids Diet (SLD), High-fat Control Diet (HCD), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…We observed only a minor effect of 2,4-TZD on fatty acid composition of the milk, including LCFA with potential positive effects on human health. Among saturated fatty acids affected by 2,4-TZD in our study, stearic acid (C18:0) and behenic acid (C22:0) are known to decrease LDL or total cholesterol in humans and mice [37,38]. Among unsaturated LCFA, proportionally more abundant in TZD vs. CTR goats, punicic acid (C18:3c9,t11,c13) can aid in combating metabolic syndrome [39], and n-7 trans-palmitoleate, abundant in dairy products (possibly the major isomers in our trans-palmitoleate), has been associated with a preventive role in diabetes [40].…”
Section: Discussionmentioning
confidence: 99%
“…We observed only a minor effect of 2,4-TZD on fatty acid composition of the milk, including LCFA with potential positive effects on human health. Among saturated fatty acids affected by 2,4-TZD in our study, stearic acid (C18:0) and behenic acid (C22:0) are known to decrease LDL or total cholesterol in humans and mice [37,38]. Among unsaturated LCFA, proportionally more abundant in TZD vs. CTR goats, punicic acid (C18:3c9,t11,c13) can aid in combating metabolic syndrome [39], and n-7 trans-palmitoleate, abundant in dairy products (possibly the major isomers in our trans-palmitoleate), has been associated with a preventive role in diabetes [40].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found that stearic acid was negatively correlated with several pro-inflammatory cytokines, ALT, and the NAS. Moreira et al (2017) suggested that behenic acid results from reduced TG absorption. Although a high concentration of oleic acid is traditionally used to induce steatosis in vitro ( Porteiro et al, 2017 ), dietary supplementation with oleic acid has been shown to exert several protective effects associated with energy homeostasis in different experimental models of NAFLD ( Lee et al, 2011 ), especially a hypocholesterolemic effect ( Ducheix et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the docosanoic acid concentration was similar between lucerne and desmanthus forages in this present study, increasing the proportion of desmanthus in the diet may have influenced docosanoic acid production through DHA biohydrogenation or stearic acid elongation. Although docosanoic acid is reported to increase serum cholesterol levels [68], its low proportion and absorption in the intestines, low bioavailability [72] and low concentration in the muscle [67] does not pose any detrimental impact on human health.…”
Section: Intramuscular Fat Content Fat Melting Point and Fatty Acids Compositionmentioning
confidence: 99%